THE MAIN CHARACTERS ANXIETY DISORDER IN THE NOVEL BLUE SKIES BY CATHERINE ANDERSON - Ulfa Norma Asyifa; Henny Suharyati; Ni Made Widisanti S (Journal Albion : Journal of English Literature, Language, and Culture, 2019)
ABSTRACTThe purpose of this research is to show the type of anxiety and the psychological impact on the main character in the novel Blue Skies by Catherine Anderson. The method used to conduct this research is descriptive analysis whilst the technique is library research. Besides that, this paper also applies intrinsic approach in the process of the analysis, such as character and characterization, setting and conflict as well as extrinsic approach which is the theory of psychoanalysis by Sigmund Freud. Carly Adams as the main character is identified to experience a lot of anxiety problems namely neurotic, realistic and morality anxiety. Those anxieties have given psychological impact on Carlys life. However, at the end, the main character is able to control her anxiety problem. Keywords : Physcological Problem, Anxiety, Psychoanalysis